2021
DOI: 10.3390/pharmaceutics13122137
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery Strategies for Curcumin and Other Natural Nrf2 Modulators of Oxidative Stress-Related Diseases

Abstract: Oxidative stress is associated with a wide range of diseases characterised by oxidant-mediated disturbances of various signalling pathways and cellular damage. The only effective strategy for the prevention of cellular damage is to limit the production of oxidants and support their efficient removal. The implication of the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway in the cellular redox status has spurred new interest in the use of its natural modulators (e.g., curcumin, resveratrol). Unfortuna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 213 publications
(295 reference statements)
0
20
0
3
Order By: Relevance
“…Some of them protect against mitochondrial dysfunction and aerobic metabolic dysfunction (102,103). Different polyphenols, such as resveratrol and curcumin, exert their effects through similar molecular targets acting on the Nuclear Factor erythroid 2-Related Factor 2 (Nrf2) pathway, suggesting that these compounds may share the same molecular pathway in lipid metabolism (104,105). At present, several studies have shown the effect of polyphenols in NAFLD (22, 106) (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Some of them protect against mitochondrial dysfunction and aerobic metabolic dysfunction (102,103). Different polyphenols, such as resveratrol and curcumin, exert their effects through similar molecular targets acting on the Nuclear Factor erythroid 2-Related Factor 2 (Nrf2) pathway, suggesting that these compounds may share the same molecular pathway in lipid metabolism (104,105). At present, several studies have shown the effect of polyphenols in NAFLD (22, 106) (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to using other natural substances as enhancers of curcumin's bioavailability, a number of different formulations have been shown to improve its uptake and stability. These include dispersions with various carriers, micronized powders, as well as nanoparticle and micellar formulations [191,192]; some of these formulations exhibit a greatly enhanced bioavailability in humans [193]. It will be interesting to systematically compare these various application forms in in vivo models with respect to their effectiveness regarding outcomes on age-and obesity-related processes fostering the development of CVDs.…”
Section: Future Directionsmentioning
confidence: 99%
“…In order to restore the oxidative balance, many antioxidant supplementation therapies (e.g., antioxidant vitamins, coenzyme Q, resveratrol, curcumin) have been implemented. However, tests of the effectiveness of such treatments in humans have raised contrasting results [ 199 , 200 , 201 ]. Some NRF2-activating compounds have been described as potential senotherapeutic drugs.…”
Section: Nrf2 and Brain (Dys)functionsmentioning
confidence: 99%